Remaining Service Life Struktur Conveyor A pada Tambang Batubara PT XYZ di Kabupaten Tanah Laut, Provinsi Kalimantan Selatan - Rihhadatul Aisyi Alfafa; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Coal transportation at PT XYZ in Tanah Laut Regency, South Kalimantan Province uses a transportation equipment such conveyors. The conveyor structure is made of low carbon steel which is susceptible to corrosion. Corrosion that occurs in the conveyor structure is caused by damage to the coating due to contact with the environment. Therefore this research was carried out on the conveyor structure with the aim of knowing the type of corrosion and corrosion control methods applied to the conveyor structure. The measurement methodology used on the conveyor structure with a length of 90 meters and 25 test points is based on thickness reduction of the conveyor structure using Ultrasonic Thickness Gauge TT 130. This measurement obtain information about the actual thickness of the conveyor structure which then becomes the input for calculating the Corrosion Rate and Remaining Life of the conveyor structure.The research conditions from 2015-2019 showed rainfall of 206.78 mm/year, air temperature of 28.09OC, and humidity of 78.78%. These environmental conditions will cause corrosion when interacting with the conveyor structure. Corrosion that occurs on the conveyor structure is a type of uniform corrosion. Corrosion control is carried out on the conveyor structure by using the three layers system coating method. This system consists of primary coating using Seaguard 5000, intermediate coating using Sherglass FF, and top coating using Aliphatic acrylic modified polyurethane. Abstrak. Pengangkutan batubara di PT XYZ di Kabupaten Tanah Laut, Provinsi Kalimantan Selatan menggunakan alat angkut berupa conveyor. Struktur conveyor yang digunakan berbahan dasar baja karbon (low carbon steel) yang rentan terjadi korosi. Korosi yang terjadi pada struktur conveyor disebabkan karena adanya kerusakan pada coating akibat kontak dengan lingkungan. Oleh karena itu dilakukanlah penelitian pada struktur conveyor dengan tujuan untuk mengetahui jenis korosi dan metode pengendalian korosi yang diaplikasikan pada struktur conveyor. Metodologi pengukuran yang digunakan pada struktur conveyor sepanjang 90 meter dan 25 test point ini berdasarkan pengurangan ketebalan struktur conveyor menggunakan Ultrasonic Thickness Gauge TT 130. Pengukuran ini membantu dalam mengetahui tebal aktual struktur conveyor yang selanjutnya menjadi input untuk perhitungan Corrosion Rate dan Remaining Service Life struktur conveyor. Kondisi penelitian dari tahun 2015-2019 menunjukkan curah hujan sebesar 206,78 mm/tahun, temperatur udara sebesar 28,09OC, dan kelembapan udara sebesar 78,78%. Kondisi lingkungan ini akan menyebabkan korosi ketika berinteraksi dengan struktur conveyor. Korosi yang terjadi pada struktur conveyor merupakan jenis korosi merata. Metode pengendalian korosi yang diaplikasikan pada struktur conveyor adalah metode coating three layers system. Sistem ini terdiri dari primer coating menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF, dan top coating menggunakan Aliphatic acrylic modified polyurethane.